Reexamining love of wisdom : philosophical desire from Socrates to Nietzsche - Flores, Juan Carlos (Cascade Books, 2016)
What is philosophy? Why does it matter? How have philosophy and its relation to religion and science changed from the ancient to the medieval and modern periods and beyond? What are the central philosophical ideas, from Socrates to Nietzsche? Reexamining Love of Wisdom addresses these questions. It offers a new perspective by organizing the material under the theme of philosophical desire and shows the timeless importance of philosophy understood as the love of wisdom. Flores provides an historical introduction to philosophy suitable for college students that is a resource for more advanced students or scholars interested in the history and nature of philosophy. -- back cover.